Posted by **Alex** on Thursday, April 11, 2013 at 9:17pm.

Having trouble verifying this identity...

cscxtanx + secx= 2cosx

This is what I've been trying

(1/sinx)(sinx/cosx) + secx = 2cosx

(1/cosx)+(1/cosx) = 2 cosx

2 secx = 2cosx

that's what i ended up with, but i know it's now right. did i mess up with the algebra?

## Answer this Question

## Related Questions

- Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...
- math - tanx+secx=2cosx (sinx/cosx)+ (1/cosx)=2cosx (sinx+1)/cosx =2cosx ...
- Calculus 2 Trigonometric Substitution - I'm working this problem: ∫ [1-tan...
- Precalculus/Trig - I can't seem to prove these trig identities and would really ...
- precal - 1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-...
- Trig - prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= ...
- Simplifying with Trigonometry Identities - Hi, I am a senior in High School ...
- trigonometry - how do i simplify (secx - cosx) / sinx? i tried splitting the ...
- Pre-Calculus - How do you verify: 1.) sinxcosx+sinx^3secx=tanx 2.) (secx+tanx)/(...
- drwls - My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an ...